Effect of Exposure to Acidic Food Items on Dentin Characteristics: An ATR-FTIR Study - Mohammad A. Alebrahim; Ahmad S. Al-Hiyasat; Ali S. Ba Rajjash (Advances in Materials Science and Engineering)
ATR-FTIR spectroscopy is a powerful technique for unraveling the fine features of dentin; however, its use in the analysis of eroded dentin remains underexplored. Herein, the impact of different acidic food products (a soft drink, vinegar, and yogurt) on dentin was investigated using ATR-FTIR spectroscopy. The durations of exposure were one, three, and seven days. One-way and two-way analyses of variance were employed to analyze differences in mean values among groups, followed by Dunnett’s and Tukey’s tests. After exposure, the mineral-to-matrix ratio in the three media was significantly lower than that in the control group. The carbonate-to-phosphate ratio and extent of crosslinking increased considerably after exposure to all media; however, the crystallinity index values decreased relative to that in the control group. These findings imply that ATR-FTIR may be an effective noninvasive technique for detecting erosion-induced changes in dentin, having a significant clinical impact on dental care.